Pedagogical advice to university professors: A career under construction - Zangali Carrasco, Ligia Bueno [UNESP]; Costa Xavier, Amanda Rezende [UNESP]; Ramos De Azevedo, Maria Antonia [UNESP] (Revista Brasileira de Orientacao Profissional, 2018)
This article undertakes a theoretical study about the professional that works with the pedagogical training of the university professor here called university pedagogical advisor. Search to make a reflection in the university a practice, developing the look on teaching as a professional exercise. In this sense, this study also aims to open the possibility of reflection and discussion about the university professor's pedagogical formation, from the view of the professional responsible for initiating the formative processes with the professors, that is, from the view of pedagogical advisor. Deepening the knowledge about this professional can be a way to review a rooted institutional culture, based on an instrumentalized and transmission teaching that still resists inside the university.
Assessoria pedagógica ao docente universitário: Uma carreira em construção
Keywords: Professional identity; Training; University pedagogical advisor